청각장애학생의 고등학교 통합교육 환경에서의 학교생활 적응에 대한 사례 연구 - 권순우(Soon-Woo Kwon) (언어치료연구, 2004)
통합교육 환경에 배치된 청각장애학생의 학교생활 적응을 위해서는 일차적으로 원만한 의사소통 능력과 평균 이상 수준의 학업성취 등을 요구하게 된다. 그러나 낮은 학업 성취도와 제한적인 의사소통 능력은 학교생활에서의 심리적 갈등과 원만하지 못한 교우관계 등으로 표출되어 결과적으로 적응에 어려움을 겪게 된다. 이와 같은 현상은 학년이 올라갈수록 더욱 심화될 것으로 예상된다. 본 연구의 참여자는 유치부부터 중학교까지는 A특수학교에 재학하였고, 그 이후에 인문계 고등학교로 통합교육을 선택하여 고등학교 3년 과정을 마쳤다. 본 연구에서는 현재 D대학교 특수교육과 1학년에 재학 중인 H학생을 대상으로 고등학교에서의 생활 적응 방법 등을 알아보고자 하였다. To adapting school life of students with hearing impairment who are placed in inclusive settings, it need to be required for them natural communication skill and above the average academic achievement. However, The level of low academic achievement and restricted communication skill bring about psychological conflicts and keepbad company in their school life. Therefore, they are to be have a difficulty in adapting their school life. The more the grade promote up, such a existing circumstances is the more deepen. The participant of the study was in A special school from kindergarten to middle school class, and then, have worked at high school inclusive settings for three years. The study is to reveal how to adapt high school life by employing H student who is now attending department of special education in D university, and is freshman. KCI Citation Count: 12